Supercritical carbon dioxide extraction of oil from Chromolaena odorata leaves / Nur Ain Zainuddin, Farahhanis Tuah and Siti Rohana Mohd Yatim - Zainuddin, Nur Ain; Tuah, Farahhanis; Mohd Yatim, Siti Rohana (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Relatively all previous researches on Chromolaena odorata were carried out by using traditional method such as hydrodistillation and soxhlet extraction methods which have their own disadvantages such as long extraction time and non-solvent free oil extract. Thus, a clean extraction method of Supercritical Fluid Extraction (SFE) using Supercritical Carbon Dioxide (SC-CO2) was proposed for the extraction of Chromolaena odorata leaves to produce oil with bioactive components. The SC-CO2 extraction of Chromolaena odorata was studied by using measurement of solubility of the oil. The extraction was conducted at constant CO2 flowrate of 24mL/min extraction time of 60 minutes within a range of temperature (40°C, 45°C and 50°C) and range of pressures (3000, 3500, 4000, 4500 and 5000 psi). The highest solubility of 7.619 mg oil/ g CO2 in SC-CO2 was obtained at pressure 4000psi and temperature 50°C. Based on the this study, the solubility increased with increases pressures because the density of CO2 that leads to the improvement of solvating power of CO2. The solubility also increased with increasing temperature as the vapour pressure of solute in the sample increased the energy for the sample to travel into the SC-CO2.